The Development of the Slovak Agricultural Landscape in a Changing World - Izakovičová, Zita; Špulerová, Jana; Raniak, Andrej (Frontiers in Sustainable Food Systems, 2022)
The agricultural landscape, which serves as a space for food production and a habitat for all kinds of living organisms, is under constant pressure to use the land in various different ways, causing constant changes in the environment. Various socio-economic, technical or political drivers have caused land use changes, which are linked to a number of socio-economic and environmental problems, e.g., different possible land uses competing with each other, changes of landscape character, increasing anthropisation of the territory and disruption of spatial ecological stability, threatening the environmental quality and causing overexploitation of natural resources. The aim of this paper is to evaluate land use changes in Slovakia since the 18th century, to identify key periods of land-management practices and prevailing drivers, and to specify the socio-economic and environmental impacts of land-use change. We organized a workshop with guided brainstorming to identify individual eras of agricultural development and their impacts. In total, we identified five main periods of agricultural landscape development and specified the characteristic landscape structure. Knowledge of the basic drivers of land use change as well as of its effects on the land is important for development of effective policies and for ensuring effective protection of the values of traditional agricultural landscape.